The language hoax : why the world looks the same in any language - McWhorter, John H. (Oxford University Press, 2014)
"Japanese has a term that covers both green and blue. Russian has separate terms for dark and light blue. Does this mean that Russians perceive these colors differently from Japanese people? Does language control and limit the way we think, such that each language gives its speakers a different 'worldview?' This opinionated book addresses the Sapir-Whorf hypothesis, which argues that the language we speak shapes the way we perceive the world. Linguist John McWhorter argues that while this idea is mesmerizing, it is plainly wrong ... McWhorter shows not only how the idea of language as a lens fails but also why we want so badly to believe it: we're eager to celebrate diversity by acknowledging the intelligence of peoples who may not think like we do. Though well-intentioned, our belief in this idea poses an obstacle to a better understanding of human nature and even trivializes the people we seek to celebrate. The reality--that all humans think alike--provides another, better way for us to acknowledge the intelligence of all peoples."--Jacket